Analysis of factors related to Burnout in Nurses in Inpatient Rooms Prof. Dr. H. Aloei Saboe Hospital - Yuyun Putriyani N. Id; Herlina Jusuf; Rachmawaty D. Hunawa (Universitas Muhammadiyah Palu, 2026)
Burnout is a common feeling of burnout that develops when individuals simultaneously experience too much stress and have too few sources of satisfaction as well as the result of energy use exceeding one's resources. This study is a type of quantitative research with a Cross Sectional approach, which consists of independent variables in the form of age, marital status, education level, working period, and workload and dependent variables of burnout. The population in this study amounted to 160 respondents with a sampling technique using Simple random sampling, a sample of 114 respondents was obtained. The instruments in this study used the Maslach Burnout Inventory (MBI) questionnaire and workload. The data analysis used is the Chi square test. The results showed that all variables studied had a significant relationship with the incidence of burnout in inpatient nurses, which was evidenced by a P-value of < 0.05 in each factor. In detail, where the age factor (P=0.035); the marital status factor (P=0.018); the education level factor (P=0.015); the work period factor (P=0.034); the workload factor (P=0.035), are the main triggers of physical and mental fatigue that collectively contribute to the burnout rate of nurses, Therefore, it can be concluded that individual characteristics and the magnitude of job demands together contribute to the level of nurse burnout in the inpatient room.